Exposure to mental health content on social media and emotional status among adolescents - Shapnah Ningrum; Aulia Rahman; Hernida Warni (Indonesian Public Health-Observer Information Forum (IPHORR) Kerjasama dengan Unit Penelitian dan Pengabdian Kep Akademi Keperawatan Baitul Hikmah, 2026)
Background: The rapid development of social media has had a significant impact on the lives of adolescents, particularly in emotional aspects. Early and middle adolescence are age groups in a phase of psychological development that is vulnerable to emotional changes due to exposure to digital content. Exposure to a variety of social media content, both positive and negative, has the potential to impact adolescents' emotional stability. Purpose: To examine exposure to mental health content on social media and emotional states among adolescents. Method: A quantitative approach with a quasi-experimental design. The sample size was 82 participants, consisting of 41 junior high school students (early adolescents) and 41 vocational high school students (middle adolescents). The sampling technique used purposive sampling. The research instrument was a questionnaire to measure the emotional status of participants. Data analysis was conducted using the Dependent T-Test and the Independent T-Test to determine the average difference in emotional status between the two groups. Results: No significant difference between the emotional status of early and middle adolescents in response to exposure to social media content, either in the pre-test (p = 0.671) with a significance value of p>0.05. Conclusion: This indicates that the level of age development does not significantly influence the emotional responses of adolescents in this study. Keywords: Early Adolescence; Emotional Status; Exposure To Social Media Content; Middle Adolescence.